Differential targeting of brain stress circuits with a selective glucocorticoid receptor modulator - Zalachoras, Ioannis; Houtman, René; Atucha, Erika; Devos, Rene; Tijssen, Ans M. I.; Hu, Pu; Lockey, Peter M.; Datson, Nicole A.; Belanoff, Joseph K.; Lucassen, Paul J.; Joëls, Marian; de Kloet, E. Ronald; et al. (Proceedings of the National Academy of Sciences - PNAS, 2013)
Glucocorticoid receptor (GR) antagonism may be of considerable therapeutic value in stress-related psychopathology such as depression. However, blockade of all GR-dependent processes in the brain will lead to unnecessary and even counteractive effects, such as elevated endogenous cortisol levels. Selective GR modulators are ligands that can act both as agonist and as antagonist and may be used to separate beneficial from harmful treatment effects. We have discovered that the high-affinity GR ligand C108297 is a selective modulator in the rat brain. We first demonstrate that C108297 induces a unique interaction profile between GR and its downstream effector molecules, the nuclear receptor coregulators, compared with the full agonist dexamethasone and the antagonist RU486 (mifepristone). C108297 displays partial agonistic activity for the suppression of hypothalamic corticotropin-releasing hormone (CRH) gene expression and potently enhances GR-dependent memory consolidation of training on an inhibitory avoidance task. In contrast, it lacks agonistic effects on the expression of CRH in the central amygdala and antagonizes GR-mediated reduction in hippocampal neurogenesis after chronic corticosterone exposure. Importantly, the compound does not lead to disinhibition of the hypothalamus-pituitary-adrenal axis. Thus, C108297 represents a class of ligands that has the potential to more selectively abrogate pathogenic GR-dependent processes in the brain, while retaining beneficial aspects of GR signaling.